Caliph Ali bin Abi Talib’s preventive policy to prevent administrative and financial corruption(35-40 AH / 655-660 AD) (Journal of the College of Basic Education, 2024)
Administrative and financial corruption is one of the problems that societies suffer from at all times, until it has become a phenomenon directed by all countries. Since its early days, Islam has increased the concept of reform, fighting corruption, and returning to everyone their right, relying on the principle of oversight and accountability, which develops what is right according to Prophetic values...and addresses what is less than that. Therefore, according to these data that Imam Ali, peace be upon him, has drawn up for us, we can without a doubt advance the administrative apparatus to strengthen the state and take care of its administrative and economic interests. Imam Ali (peace be upon him) was the first to plan and design an elaborate administrative system. Through which jobs were defined, a precise approach to prevention and follow-up was followed, and the principle of accountability was adopted with a solid prevention system to prevent administrative and financial corruption.